UJI AKTIVITAS SELULOLITIK DARI TIGA ISOLAT BAKTERI Bacillus sp. GALUR LOKAL RIAU - Rahayu, Ariani Gusti; Haryani, Yuli; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulolytic bacteria are bacteria that have ability to hydrolize cellulose into smaller oligosaccharides and into glucose units. Glucose is used as a source of carbon and energy for bacterial growth. The aims of this study wasto determine the ability of three bacillus sp. bacteria from rhizosphere of mustard plants (Bacillus sp. B1), rhizosphere of rice plants (Bacillus sp. B2), and peat soil of Giam Siak Kecil (Bacillus sp. B3) to produce cellulase enzymes based on clear zone which is seen surrounding the colonies. Cellulolitic activity of the bacteria was determined by their ability bacteria to degrade carboxymethyl cellulose (CMC) substrate. The results showed that all isolates tested were able to produce cellulase. Bacillus sp. B1 isolate had the highest cellulolitic activity [(6.502 Â± 0.462) x 10 -3 U/mL] than 2 isolates based on 24 hourproduction time and120 rpmspeed of agitation.